INTERACTIVE METHODS IN TEACHING THE RUSSIAN LANGUAGE (International journal of artificial intelligence, 2024)
In the ever-evolving landscape of language education, it is important to include interactive teaching methods to engage students, promote active learning, and increase language proficiency. When it comes to teaching Russian, interactive approaches play a crucial role in making the learning process dynamic, interesting and effective. In this article, we look at different interactive teaching methods that can be used to enrich Russian language learning and develop students' language skills with enthusiasm and confidence.